Quantitative Assessment of the Number of Escherichia Coli Bacteria and Risk Characterization of Food in Cafeteria of Regional Public Hospital Kendari City - saflia, Ismiliani; Mallongi, Anwar; Hatta, Muh.; Ishak, Hasanuddin; Birawida, Agus; Thamrin, Yahya (International Journal Papier Advance and Scientific Review, 2020)
One of the cases of disease originating from food is commonly called foodborne disease which is caused by pathogenic microorganisms or microbes that contaminate food. For this reason, it is necessary to calculate a quantitative microbial risk analysis to see the risk of disease caused by bacteria. This study aims to analyze the quantitative risk of Escherichia coli bacteria in food at the Kendari City Hospital canteen against public health problems. This study used an observational method with a cross sectional approach. This study uses a Quantitative Microbial Risk Assessment (QMRA) approach. The samples in this study were each type of food including rice, vegetables, tofu, chicken and fish as well as tea drinks which were taken by accidental sampling. The results showed that the number of Escherichia coli bacteria in the morning food on the first, second and third day was found in tofu, vegetables, chicken at 3.6 CFU / g and in drinks 3 CFU / ml. The number of Escherichia coli bacteria during the day on the first day was found in vegetables at 6.1 CFU / g, on the second day on vegetables was 9.2 CFU / g, and on the third day in chickens was 14 CFU / g. Characterization of bacterial risk in respondents due to consumption of food in the morning and during the day, shows that Pill = 3.5 x 10-1 which means that food samples positive for Escherichia coli bacteria have a high risk of causing health problems in humans such as diarrhea and disorders other health.